2011
DOI: 10.1186/1471-2318-11-1
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of renal function in relation to the use of drugs in elderly in nursing homes; a cohort study

Abstract: BackgroundRenal function decreases with age. Dosage adjustment according to renal function is indicated for many drugs, in order to avoid adverse reactions of medications and/or aggravation of renal impairment. There are several ways to assess renal function in the elderly, but no way is ideal. The aim of the study was to explore renal function in elderly subjects in nursing homes and the use of pharmaceuticals that may be harmful to patients with renal impairment.Methods243 elderly subjects living in nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 34 publications
3
51
1
4
Order By: Relevance
“…In addition, certain centers of the brain associated with dual-task processing showed less activation posttraining, implying reduced processing demands posttraining 102. Some studies have also implied this training maneuver to act as a cognitive therapy for patients with attentional deficits and cognitive impairments 34,52. Furthermore, this review identified dual-task training regimes to also allow benefits in cognitive performance 38,52.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, certain centers of the brain associated with dual-task processing showed less activation posttraining, implying reduced processing demands posttraining 102. Some studies have also implied this training maneuver to act as a cognitive therapy for patients with attentional deficits and cognitive impairments 34,52. Furthermore, this review identified dual-task training regimes to also allow benefits in cognitive performance 38,52.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies have also implied this training maneuver to act as a cognitive therapy for patients with attentional deficits and cognitive impairments 34,52. Furthermore, this review identified dual-task training regimes to also allow benefits in cognitive performance 38,52. According to Hiyamizu et al36 and Wollesen and Voelcker-Rehage,38 enhancements in cognitive performance might lead toward smoothening of cognitive activities while maintaining static and dynamic postures, resulting in preventing falls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This main effect of age is typically interpreted as reflecting a decrease in the overall capacity for information processing or a decline in the executive management of such resources (Craik et al, 2010; Tombu and Jolicæeur, 2003). In healthy older adults as well as patients with PD, impairments in a range of measures of divided as well as sustained attentional performance are a robust predictor for freezing of gait and falls (Allcock et al, 2009; Lord et al, 2010; Naismith et al, 2010; O’Halloran et al, 2011; Persad et al, 2008; Woollacott and Shumway-Cook, 2002; Yarnall et al, 2011). …”
Section: Aging and Pd-associated Impairments In Attention And Loss Ofmentioning
confidence: 99%
“…Generally serum creatinine is one of the parameters to measure the kidney function. However, this is inaccurate in geriatrics due to muscle breakdown, and they have a moderate decrease in renal function 9,10 . Creatinine clearance is a valid predictor of nephritic function.…”
mentioning
confidence: 99%